2018
DOI: 10.1007/s12040-018-0972-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced residual mean circulation during the evolution of split type sudden stratospheric warming in observations and model simulations

Abstract: Residual mean circulation changes during the evolution of sudden stratospheric warming (SSW) are investigated by composite analyses of 76 major warming events identified in a present day simulation performed with a coupled ocean-troposphere-stratosphere model from 299 winters. Their dynamical signatures are compared with the 17 SSW events identified from 35 years of Era-Interim data. The main difference is that, relative frequency of simulated SSW events is smaller than that obtained from reanalysis. SSW event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…RMC is widely used for analyzing the global mass transfer and passive/long-lived atmospheric species, as well as the thermodynamic regime of the atmosphere. Moreover, the RMC dependence on planetary waves makes the transformed Eulerian approach a convenient method for analyzing and interpreting nonstationary interactions of PWs with the mean flow [Bal et al, 2018;Koval et al, 2023]. An important characteristic that allows us to analyze PW and to interpret the interaction of the wave with the mean flow is the Eliassen-Palm (EP) flux…”
Section: Residual Meridional Circulationmentioning
confidence: 99%
“…RMC is widely used for analyzing the global mass transfer and passive/long-lived atmospheric species, as well as the thermodynamic regime of the atmosphere. Moreover, the RMC dependence on planetary waves makes the transformed Eulerian approach a convenient method for analyzing and interpreting nonstationary interactions of PWs with the mean flow [Bal et al, 2018;Koval et al, 2023]. An important characteristic that allows us to analyze PW and to interpret the interaction of the wave with the mean flow is the Eliassen-Palm (EP) flux…”
Section: Residual Meridional Circulationmentioning
confidence: 99%
“…Some differences in the wind vectors in the upper troposphere can be connected with rather schematic representation of the tropospheric dynamics in the model. Birner and Bönisch (2011) calculated the RMC based on the data from the Canadian Middle Atmosphere Model and obtained streamline distributions for January, which reflect the RMC structure shown in Fig. 2a.…”
Section: Calculating the Residual Mean Meridional Circulationmentioning
confidence: 99%
“…Using data from the reanalysis of meteorological information, Song and Chun (2016) considered the contributions of various terms of the transformed Eulerian equations of temperature and angular momentum to the RMC formation at different SSW stages. Bal et al (2017) studied the changes in the RMC based on the analysis of 76 model SSWs and of 17 major SSWs selected from the ERA-Interim reanalysis data. In both studies mentioned above, it was confirmed that large-scale wave disturbances are the main driving force of the RMC due to the transfer of energy and angular momentum in the middle atmosphere and the MLT region.…”
Section: Residual Circulation At the Different Ssw Stagesmentioning
confidence: 99%